COMPONENTES Y DINÁMICA NATURAL DEL AMBIENTE -CIUDAD DE NEUQUÉN- - Olga C. Capua; Elsie M. Jurio (Boletín Geográfico)
The city of Neuquen, capital of the province, is located on the valleys' soils product or Limay and Neuquén rivers and on the surface, slopes and foothills of the plateau, located north of the town center. Up to 70s decade urban region was surrounded by agricultural areas, with intensive irrigation infrastructure and limited by rivers and relief with a marked topographic steep slope dissected by a dense network of rills and gullies. This front has layers with different resistance, then, a stepped profile with a succession of cliffs and debris cones that provide a complex look of the terrain. For a best understanding of nature and proper land management is essential to study the natural dynamics of dry regions. This demonstrates the diversity of morphogenetic processes responsible for the current modeling. Under the prevailing climatic conditions, soil pedogenic processes are weak or allowing the initial processes of weathering or weathering, act directly on the rocky outcrops influencing modeling. The mechanical breakdown and gravitational movements, generate from the initial slope, new landforms characterized by the deposition of debris, masking en some sectors, the original lithology. This is compounded by the action of running water, where runoff, predominantly concentrated, is based on two fundamental values: the intensity of rainfall, and the rate of infiltration. Low rainfall and intense evapotranspiration define a framework characterized by a homogeneous sparse shrub steppe, with elevated percentages of bare soil. Furthermore, the scarse plant covering and soil characteristics favor the direct action of wind on the surface incrementing the processes of erosion-deflation, abrasion and attrition, and build farms. This paper considers the interaction of biophysical elements of nature (climate, topography, vegetation, soil, water), agents and processes generating the forms of relief, in a systemic approach to understand the natural dynamics, to preserve balance and to generate the basis to elaborate land use strategies.